2008
DOI: 10.1002/nem.695
|View full text |Cite
|
Sign up to set email alerts
|

QoS experiences in native IPv6 networks

Abstract: SUMMARYDeployment of IPv6 technology in research and commercial networks has accelerated in the last few years. Inevitably, as more advanced services take advantage of the new technology, IPv6 traffi c gradually increases. Today, there is limited experience in the deployment of Quality of Service (QoS) for IPv6 traffi c in backbone networks that support the Differentiated Services framework. As available software and hardware are designed to handle IPv4 packets, there is a need to accurately measure and valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Previous work has investigated QoS performance of native IPv6 connectivity when utilizing Diffserv architecture in a test network [5]. This work concluded that IPv4 and IPv6 performance guarantees were identical when implemented in Cisco gigabit Ethernet routers but older line cards showed IPv6 performance was worse.…”
Section: Related Workmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous work has investigated QoS performance of native IPv6 connectivity when utilizing Diffserv architecture in a test network [5]. This work concluded that IPv4 and IPv6 performance guarantees were identical when implemented in Cisco gigabit Ethernet routers but older line cards showed IPv6 performance was worse.…”
Section: Related Workmentioning
confidence: 92%
“…The last noticeable gap is the lack of studies utilizing real hardware devices, with the notable exception of [5]. The majority of studies utilize modelling and simulation tools for simplified deployment.…”
Section: Rationale For This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, introduction of flow label field was further major change in IPv4 header for QoS purpose [9]. In addition to huge address space, IPv6 puts forward an important enhancement with respect to built-in security, mobility, auto-configuration and enhanced multicast support [10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to strengthen the existing architecture of Internet Protocol, IETF has developed Internet Protocol version 6 (IPv6) [1]. IPv6 offers a significant improvement over IPv4 when it comes to the unlimited address space, the built-in mobility and the security support, easy configuration of end systems, and enhanced multicast features, etc [2]. On the other hand, due to the fascination of end users of the World Wide Web (WWW) and the popularity of real-time applications, we can now observe new increasing demands on real-time multimedia services over the Internet.…”
Section: Introductionmentioning
confidence: 99%